Effects of early mathematics intervention for low-SES pre-kindergarten and kindergarten students: a replication study. Issue 1 (17th February 2022) - Starkey, Prentice; Klein, Alice; Clarke, Ben; Baker, Scott; Thomas, Jaime
ABSTRACT: A socioeconomic status (SES)-related achievement gap in mathematics emerges prior to school entry, and increases in elementary school. This gap makes implementation of demanding mathematics standards (e.g., the Common Core State Standards) an ongoing challenge. Early educational intervention is a strategy for addressing this challenge. A randomised controlled trial was conducted in public American preschools to (1) replicate the efficacy of an intervention, Pre-K Mathematics, for low-SES children, and (2) test the combined impact of this intervention and a Common-Core-aligned kindergarten intervention, Early Learning in Mathematics . Forty-one clusters of pre-kindergarten and kindergarten classrooms, containing a sample of 389 low-SES children from an agricultural region, were randomly assigned to treatment and control conditions. The original impact findings were replicated: Child mathematics outcomes in pre-kindergarten were positive and significant. Gains were maintained in kindergarten. Thus, the gap can be reduced and gains maintained by sustained early intervention.